Clinical Performance of Bulk-Fill Versus Incremental Composite Restorations in Primary Teeth: A Systematic Review of In Vivo Evidence - Maria Sarapultseva; Desheng Hu; Alexey Sarapultsev (Dentistry Journal)
Background and Objectives: This is the first systematic review to focus exclusively on in vivo randomized controlled trials that compare bulk-fill and conventional incremental composite restorations in primary teeth. Our aim was to synthesize current evidence on their clinical performance, including retention, two-year survival rates, marginal integrity, and procedural efficiency. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and the Elicit AI platform up to March 2025. Eligible studies were in vivo randomized controlled trials involving children aged 3–12 years with carious primary teeth, directly comparing bulk-fill and incremental composite restorations. Primary outcomes included retention rates, two-year survival, and marginal integrity, while secondary outcomes were postoperative sensitivity, secondary caries, and aesthetic outcomes. Two reviewers independently performed study selection, data extraction, and risk-of-bias assessments using the Cochrane RoB 2.0 tool. A narrative synthesis was undertaken due to substantial heterogeneity in study design and outcome reporting. The review protocol was registered in PROSPERO (CRD420251021433). Results: Thirteen randomized controlled trials met the inclusion criteria. Both restoration techniques demonstrated high short-term retention rates (>90%) and comparable two-year survival (85–90%). Marginal integrity was generally equivalent, though incremental techniques showed modest advantages in complex cavities. Secondary outcomes were inconsistently reported, with no significant group differences. Bulk-fill restorations consistently reduced the procedural time by 2–4 min per restoration, representing a meaningful advantage in pediatric clinical settings. Conclusions: Bulk-fill composites offer a clinically effective and time-efficient alternative to incremental layering in the restoration of primary teeth. This focused synthesis addresses a gap in existing reviews by concentrating solely on primary dentition and in vivo evidence. Despite similar clinical outcomes, the time savings associated with bulk-fill techniques may enhance their utility in pediatric dentistry. Further standardized and long-term trials are warranted to confirm these findings and inform clinical guidelines.